Needs and access to health services by people in post-COVID-19 Condition in Brazil: a qualitative study - Kelly Laste Macagnan; Teila Ceolin; Caroline Vasconcellos Lopes; Vanessa de Araujo Marques; Juliana Graciela Vestena Zillmer (O Mundo da Saúde)
Post-COVID-19 condition involves persistent symptoms that impact quality of life and require ongoing care. This study aimed to identify the health needs and health care services used by individuals in post-COVID-19 condition, as well as to describe the costs borne by the users. This is a qualitative study conducted at the post-COVID outpatient clinic of a teaching hospital in the city of Pelotas, Rio Grande do Sul, Brazil. Ten families participated, comprising ten individuals in post-COVID-19 condition and ten family members, totaling twenty participants. The sample was intentional, and data collection took place between March and August 2022 through semi-structured interviews. Data were organized using the IRAMUTEQ software and analyzed through content analysis. Individuals in post-COVID-19 condition presented health needs that made them dependent on family care and required multidisciplinary care. They accessed different services within the SUS care network, as well as private services paid for out-of-pocket, such as medical consultations, physical therapy, tests, and medication purchases. People in post-COVID-19 condition require continuous care, both in primary and specialized care, with a multidisciplinary team for rehabilitation, prevention of functional dependency progression, and new complications.